Полет над миром: [стихи всем странам мира] / Владимир Тяптин - Тяптин Владимир Яковлевич (Проект, 2016)
Экземпляры: СБ (20171018) / Инвентарный номер: 54773 / Цена: 75.00 / Сис.шифр: Р2 / Авт.знак: Т 99 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6